Ethnomathematics in Culinary Practices: Getuk Pisang as Mathematical Learning Medium for Early Childhood - Shelline Eviani Shirly; Suharti Suharti; Kartika Rinakit Adhe (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This qualitative ethnographic study explores ethnomathematics within the local culinary tradition of Getuk Pisang as a learning medium for children aged 4–7 in Kediri. The study involves five participants: two children aged 4, two aged 5, and one aged 7. All participants, except the 7-year-old child who assists their parents in selling, are enrolled in early childhood education (PAUD). The research is motivated by the limited integration between formal mathematics and children’s concrete cultural experiences. Data were collected through observations and interviews with parents and analyzed using the interactive model of Miles et al. The findings identify mathematical concepts embedded in Getuk Pisang, including geometry, non-standard measurement, number sense, and seriation. Children demonstrate an intuitive understanding of these concepts through contextual interaction. The study suggests that local culinary traditions can serve as effective learning media to reduce mathematics anxiety and enhance cognitive engagement.